2016
DOI: 10.1039/c6ta03164a
|View full text |Cite
|
Sign up to set email alerts
|

High-performance flexible and air-stable perovskite solar cells with a large active area based on poly(3-hexylthiophene) nanofibrils

Abstract: Flexible metal halide perovskite solar cells (PSCs) have been considered promising wearable energy power sources. Recently, various multi-functional charge-transporting layers, with high conductivity and air stability, have been rapidly developed in order to improve device performance. The practical use of flexible PSCs requires the retention of the performance and air stability at large active areas. However, increasing the size of the active layer results in increased contact and series resistance at the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…We further optimizedt he thickness of 10 %Z MO layers for optimization of the device performance. [36] To correlatet he Mg doping and the resultant PSC performance, measurements of optical absorption, photoelectron spectroscopy,a nd electrical impedance were carriedo ut. ZMO films with 10, 25, and 40 nm thickness were prepared by using varied precursor sol concentrations of 0.2, 0.4, and 0.6 m in spin coating, respectively.F igure S5 gives the J-V characteristicso ft he PSCs based on varied ZMO thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further optimizedt he thickness of 10 %Z MO layers for optimization of the device performance. [36] To correlatet he Mg doping and the resultant PSC performance, measurements of optical absorption, photoelectron spectroscopy,a nd electrical impedance were carriedo ut. ZMO films with 10, 25, and 40 nm thickness were prepared by using varied precursor sol concentrations of 0.2, 0.4, and 0.6 m in spin coating, respectively.F igure S5 gives the J-V characteristicso ft he PSCs based on varied ZMO thickness.…”
Section: Resultsmentioning
confidence: 99%
“…This reduced hysteresis suggests that there might be al ower contact resistance at the ZMO/perovskite interface and the Mg doping provides improved charge extraction from the perovskite. [36] To correlatet he Mg doping and the resultant PSC performance, measurements of optical absorption, photoelectron spectroscopy,a nd electrical impedance were carriedo ut. Given that the shield effect of the ITO substrate causes difficulty in identifying the absorption edges from the transmission spectra, [34] we measuredt he transmission spectra of all ZMO films on quartz glass to determine the band gaps.…”
Section: Resultsmentioning
confidence: 99%
“…[200] Li-doped P3HT nanofibrils (LP-P3HT)-based flexible PSCs exhibited good mechanical stability (retaining a PCE of 12.96% after 500 bending cycles at r=15 mm) and air stability (retaining 87% of the initial PCE after storage in ambient condition (30% RH) for 30 d). [201] Kazunari Matsuda et al [202] reported an all carbon SWNT/GO/PMAA HTMbased PSC, exhibiting significantly enhanced stability (PCE changing slightly from 10.5% to 10.0% during 10 days storage in air (70-80% RH) at room temperature) in comparison with spiro-OMeTAD based device (PCE declining from10.5% to 5.8% in the same condition). Introducing hydrophobic alkyl chains into HTMs can improve the stability of the PSCs because of the enhanced moisture resistance of the HTMs.…”
Section: Hydrophobic Organic Semiconductor As Htmmentioning
confidence: 99%
“…PCBM film might be the most frequently used fullerene derivative ETL in PSCs, because it not only can be simply prepared by a spin‐coating process without any further treatment but also reduce the density of trap states and passivate the grain boundaries of the perovskite absorber. So far, n‐i‐p type FPSCs with PCEs of 11.1–13.12% have been reported by several groups using different HTLs . As shown in Figure a, an extremely thin layer of PEIE was used to modify the surface of the TCO in such devices, which was believed to decrease the surface work function of ITO and facilitate electron extraction into the electrode via fullerene derivatives (Figure b) .…”
Section: Carrier Transport Layersmentioning
confidence: 99%